Exploring effective teacher professional development programs in private kindergartens: a case study in Shanxi, China - Bingjie, Wei; Abdullah, Arnida; Saharuddin, Norzihani (Human Resources Management Academic Research Society (HRMARS), 2024)
This qualitative study examines effective teacher professional development programs in private kindergartens, focusing on a case study in Shanxi, China. Utilizing data from interviews and observations, the research explores the characteristics and determinants of these programs. Findings highlight key elements contributing to program efficacy, including curriculum design, implementation strategies, and teacher perspectives. Despite their significance, challenges such as resource constraints and institutional support are also identified. The study underscores the importance of tailored professional development initiatives in enhancing educational outcomes within private kindergarten settings.